The Effect of Inflation, Firm Age, and Firm Size on Profitability (Case Study on Non-Cyclical Consumer Goods Sector Companies Listed on the Indonesia Stock Exchange for the 2019-2023 Period) - Anyelir Anyelir; Edi Firdaus; Hadi Purnomo; Syaira Zahra Anjani; Alisya Nathaniela (Program Studi Keuangan & Perbankan, Fakultas Ekonomi dan Bisnis, Universitas Komputer Indonesia, 2026)
This study aims to determine the effect of inflation, firm age, and firm size, both partially and to determine each the development of each variable in Consumer Non-Cyclicals Sector Companies the 2019-2023 period. The research method used is a descriptive and verifiable method with a quantitative approach. The data used are secondary data, including Inflation, Firm Age, Firm Size, and Profitability data. The sample used in this study consists of of financial statements from the 2019 to 2023 period, with 6 companies comprising a total of 30 samples. The statistical tests conducted include multiple linear regression analysis, classical assumption tests, correlation analysis, determination coefficient analysis, and hypothesis testing using SPSS 25 for Windows. Based on the results of the T-test in this study, inflation has a negative and insignificant effect on company profitability, company age has a positive and significant effect, company size has a negative and significant effect. effect, and the F-test results indicate that inflation, firm age, and firm size have an effect on profitability. Keywords: Inflation; Firm Age; Firm Size; Profitability; Consumer Non-Cyclicals Sector Companies